ANALISIS HASIL BELAJAR SISWA SMK JURUSAN JASA BOGA TERHADAP MINAT BEKERJA SISWA PADA INDUSTRI HOSPITALITY DAN PARIWISATA DI JAKARTA - Yudhiet Fajar Dewantara (Bogor Hospitality Journal, 2020)
The purpose of this study was to determine whether there is an effect of student learning outcomes in the Department of Catering on Interest in Working in Hospitality and Tourism which includes cognitive, affective and psychomotor abilities in subjects related to Normative, Adaptive and Productive. Results and Discussion From the results of simple regression analysis there is a positive relationship between learning outcomes and interest in working, the higher learning outcomes, the more interest in work. Hypothesis Test Results Normative dimension with t count > t table (9,174 > 1,98422) and significance value < 0.05 (0.00 < 0.05), so Ho is rejected and Ha is accepted. Hypothesis Test Results "Adaptive dimension, with a value of t count < t table (1.116 < 1.98422) and a significance value of > 0.05 (0.267 > 0.05). And Test Results "Dimensional productive, with a value of t count > t table (5.581 > 1.98422) and a significance value of <0.05 (0.00 <0.05), so Ho is rejected and Ha is accepted. Meanwhile, for the F test with a calculated F value > F table (81,638 > 3,94) or a significance value < 0.05 (0.00 < 0.05) so Ho is rejected. “Together (simultaneously) each of the normative, adaptive, and productive dimensions in learning outcomes has a significant effect on students' work interest in Food Processing, Bread and Cake Processing, Food and Beverage Services, Excellent Service, Tourism, Nutrition Sciences. , Hygiene Sanitation. Research suggestions for students are expected to be serious in participating in activities or training regarding practices related to their respective majors, be serious in doing assignments or exercises, besides that students can reproduce information on the business world/industrial world via the internet to increase student capacity.